Nanofluids Used in Photovoltaic Thermal (PV/T) Systems: a Review - A. Sachit, F.; A.M. Rosli, M.; Tamaldin, N.; Misha, S.; L.Abdullah, A. (International Journal of Engineering and Technology, 2018)
Solar energy has attracted increasing research attention, particularly to improve and develop new small-sized devices with high energy efficiency or to establish appropriate techniques to produce such devices. These materials should be effectively utilised to enhance solar energy system performance. Nanofluids exhibit potential for heat transfer and absorption. This paper reviews studies on nanofluids used in solar energy systems, specifically photovoltaic thermal (PV/T) systems. The implementation of solar collector and PV/T system variables without or with nanofluids is also discussed. This paper is divided into two sections. The first part reports theoretical and experimental outcomes of analyses on thermal conductivity, density, specific heat and heat transfer coefficientof nanofluids. Thermophysical characteristics of nanofluids have been widely investigated to study the influence of these materials on the performance of solar collector and PV/T systems. The second part discusses nanofluid applications in photovoltaic thermal PV/T solar systems and solar collector. Nanofluids can be utilised to improve the performance of different solar thermal systems, particularly photovoltaic thermal systems, and thus increase the overall solar energy yield.Â